Diagnostic value of post bronchoscopic sputum and bronchoscopy guided cytology in diagnosing pulmonary lesions - Rao, Mekhala; Dinesh, U S; S, Sanjay; Athanikar, Vidisha S (Journal of Pathology of Nepal, 2025)
Background: Lung cancer is the main cause of cancer deaths in developing countries. The use of cytology in the diagnosis of cancer of the respiratory tract is one of the most useful applications of bronchoscopy.  The objective of this study was to evaluate the cytomorphological features of post-bronchoscopy sputum and bronchoscopy-guided cytology samples, including bronchial wash, bronchial brush, and bronchoalveolar lavage, and to compare these with bronchoscopic biopsies.Materials and Methods: It was a prospective cross-sectional study conducted over 2 years (1st June 2019 to 31st May 2021). All PBS samples, BW, bronchial brushes, BAL, and bronchoscopic biopsies obtained from patients of all age groups received in the pathology laboratory of SDM College of Medical Sciences and Hospital were included in the study. In addition, bronchoscopy reports and CT scan reports were obtained.Results:  A total of 181 cytology samples were collected from 111 patients. The average age was 52.2 years, with 76 (68.47%) patients being males, and 35 (31.53%) patients being females. Infectious diseases like actinomycosis, mucormycosis, tuberculosis, and candidiasis were diagnosed. The most common malignancy diagnosed by cytology was adenocarcinoma. The diagnostic accuracy of bronchial brush was 93.75%, bronchial wash and /or bronchoalveolar lavage was 78.72%, while for post-bronchoscopy sputum, the diagnostic accuracy was 52.17%.Conclusions: Cytology samples can be used as a reliable diagnostic tool in the diagnosis of both non-neoplastic and neoplastic pulmonary lesions.